Effects of Ellagic Acid on Myocardial Contractility in Isolated and Perfused Rat Hearts - Giada Benedetti; Leonardo Carbonetti; Vincenzo Calderone; Lara Testai (Biomedicines)
Background/Objectives: Ellagic acid (EA) is a polyphenol found in several fruits and vegetables, including pomegranate, nuts and berries. It exhibits significant health benefits, mainly cardio- and vaso-protective; indeed, EA protects the myocardium against infarction and inhibits cardiac fibrosis. These beneficial effects may be, at least in part, promoted by calcium release from and uptake by the sarcoplasmic reticulum, which are crucial events for cardiac relaxation and contraction. Regardless, the exact mechanism is currently unclear. Methods: A deeper investigation of the role of EA in cardiac contractility and the underlying mechanism has been carried out by using an ex vivo model of isolated and perfused rat heart. Results and Discussion: EA perfusion (100 nM–10 µM) did not influence the coronary flow (CF), suggesting the absence of a vasoactivity, but significantly increased contractility parameters (LVDP and dP/dt). Interestingly, a more marked effect of EA on LVDP and dP/dt values was observed when it was perfused in the presence of AngII. Cyclopiazonic acid (CA) and red ruthenium (RR), specific antagonists of SERCA and RyRs, respectively, were used to explore the contribution of EA when the intracellular calcium handling was altered. In the presence of CA, EA, perfused at increasing concentrations, showed a very modest positive inotropism (significant only at 1 µM). Instead, RR, which significantly compromised all functional parameters, completely masked the effects of EA; furthermore, a marked reduction in CF and a dramatic impact on the positive inotropism occurred. Conclusions: These results demonstrate the positive inotropism of EA on isolated and perfused hearts and suggest that the RyRs may be a main target through which EA plays its effects, since inhibition with RR almost completely blocks the positive inotropism.